Początkowe stadia życia ludzkiego według św. Pawła - Andrzej Muszala (Polonia Sacra)
The article makes an attempt to decode the concept of the human conception in the mothers womb represented by the Apostle of Nations. His opinion in this issue is based on two fragments from the Old Testament: Jb 10: 8–10 and Ps 139: 13–16. They represent the one seed theory, saying that a new man is formed only from the man’s seed; the role of the mother comes down to be a container receiving male semen. They also express a conviction, that every human life is under God’s special protection from the very beginning. Therefore it demands a total respect, the same respect as for a child already born. The article analyze also three expressions of embryological meaning, used by St. Paul: “from the mother’s womb” (ἐκ κοιλίας μητρός; Ga 1: 15), “Christ is formed in you” (μορφωθῇ; Ga 4: 19) and “child born abnormally” (ἔκτρωμα; 1 Kor 15: 8).